2014
DOI: 10.2138/am-2015-5003
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of sulfur isotope fractionation in pyrite-type disulfides

Abstract: The sulfides are an important group of minerals. As a geochemical tracer, the sulfur isotope fractionation in sulfides can be used to analyze the ore-forming process and the ore-forming material source. Fe, Co, Ni, and Mn are the first row transition metals, and pyrite (FeS 2 ), cattierite (CoS 2 ), vaesite (NiS 2 ), and hauerite (MnS 2 ) crystallize in the pyrite-type structure. However, there are few studies on the sulfur isotope fractionation in these disulfides. So studying the isotope fractionation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 55 publications
1
16
0
3
Order By: Relevance
“…6а, результаты на-стоящей работы хорошо согласуются с расчетами из первых принципов на основе функционала плотности (Liu et al, 2015;, с другой стороны, наблюдается существенное расхождение с более ранними результатами (Blanchard et al, 2009), также выполненными в рамках подхода, основанного на использовании функционала электронной плотности. В более поздних работах (Liu et al, 2015; использовалось приближение, не требующее введения масштабирующего множителя (scaling factor) для согласия расчетных и наблюдаемых фундаментальных частот тепловых колебаний. Первые оценки 34 S/ 32 S β-фактора пирита на основе мессбауэровской спектроскопии и теплоёмкости также оказались неточными, т.к.…”
Section: S/ 32 S β-факторы для пиритаunclassified
See 2 more Smart Citations
“…6а, результаты на-стоящей работы хорошо согласуются с расчетами из первых принципов на основе функционала плотности (Liu et al, 2015;, с другой стороны, наблюдается существенное расхождение с более ранними результатами (Blanchard et al, 2009), также выполненными в рамках подхода, основанного на использовании функционала электронной плотности. В более поздних работах (Liu et al, 2015; использовалось приближение, не требующее введения масштабирующего множителя (scaling factor) для согласия расчетных и наблюдаемых фундаментальных частот тепловых колебаний. Первые оценки 34 S/ 32 S β-фактора пирита на основе мессбауэровской спектроскопии и теплоёмкости также оказались неточными, т.к.…”
Section: S/ 32 S β-факторы для пиритаunclassified
“…По данным мессбауэровской спектроскопии и теплоёмкости определены β-факторы серы для пирита. Полученные 34 S/ 32 S β-факторы хорошо согласуются с расчетами из первых принципов (Liu et al, 2015;. В то же время аналогичные расчеты (Blanchard et al, 2009) приводят к более высоким значениям 34 S/ 32 S β-факторов для пирита.…”
Section: выводыunclassified
See 1 more Smart Citation
“…Several researchers have carried out experimental measurements of fractionation between pyrite and other sulphides,such as: ZnS-PbS-FeS2-S (Grootenboer andSchwarcz, 1969), FeS2-ZnS-PbS (Kajiwara et al, 1969;Smith et al, 1977), FeS2-CuFeS2-PbS-ZnS (Kajiwara andKrouse, 1971), FeS2-PbS-S (Salomons, 1971), and some sulphide minerals-H2S system (Ohmoto and Rye, 1979;Ohmoto and Goldhaber, 1997). In contrast, theoretical calculations have not been reported except for in the studies of Polyakov et al (2007), Blanchard et al (2009), Polyakov and Soultanov (2011), and Liu et al (2015). Furthermore, there are scarcely any studies on S isotope fractionation in transition metal sulpharsenides and sulphantimonides.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that the first-principles calculation based on density functional theory is a powerful tool for calculating the isotope fractionation factors for a variety of isotope systems including H, O, Mg, Ca, Si, S, Fe, Ge and Se (Balan et al, 2014;Blanchard et al, 2009;Feng et al, 2014;Huang et al, 2014;Liu, 2010, 2011;Liu et al, 2014Liu et al, , 2015Méheut et al, 2009Méheut et al, , 2010Méheut and Schauble, 2014;Reynard and Caracas, 2009;Schauble, 2011;Wu et al, 2015). In this study, this approach is used to investigate the equilibrium S isotope fractionation in the sulpharsenides and sulphantimonides of Fe, Co and Ni.…”
Section: Introductionmentioning
confidence: 99%